Validation of the Brazilian-Portuguese Version of the Clinician Administered Post Traumatic Stress Disorder Scale-5 - Oliveira-Watanabe, Thauana Torres; Ramos-Lima, Luis Francisco; Zylberstajn, Cecilia; Calsavara, Vinicius; Coimbra, Bruno Messina; Maciel, Mariana Rangel; Freitas, Lucia Helena Machado; Mello, Marcelo Feijo; Mello, Andrea Feijo (Frontiers in Psychiatry, 2021)
Objectives: The aim of this study was to validate CAPS-5 for the Brazilian-Portuguese language on a sample of 128 individuals from two centers (from the cities of São Paulo and Porto Alegre) who have been recently exposed to a traumatic event. Methods: We performed a reliability analysis between interviewers (with a subset of 32 individuals), an internal consistency analysis, and a confirmatory factorial analysis for the validation study. Results: The inter-rater reliability of the total PTSD symptom severity score was high (intraclass correlation coefficient=.994, 95% CI [.987–.997], p<.001). Cohen’s Kappa for individual items ranged between .759 and 1. Cronbach’s alpha coefficients indicated high internal consistency for the CAPS-5 full scale (α=.826) and an acceptable level of internal consistency for the four symptom clusters. The confirmatory factorial analysis for the 20-item original CAPS-5 did not fit the data well. A 15-item model with better results was then established by excluding the following CAPS-5 items: dissociative amnesia, recklessness, distorted cognitions, irritability, and hypervigilance. Conclusion: The model with only 15 items provided a good fit to the data with high internal consistency (α=.835).